2011
DOI: 10.1103/physrevb.83.060415
|View full text |Cite
|
Sign up to set email alerts
|

Chirality control via double vortices in asymmetric Co dots

Abstract: Reproducible control of the magnetic vortex state in nanomagnets is of critical importance. We report on chirality control by manipulating the size and/or thickness of asymmetric Co dots. Below a critical diameter and/or thickness, chirality control is achieved by the nucleation of single vortex. Interestingly, above these critical dimensions chirality control is realized by the nucleation and subsequent coalescence of two vortices, resulting in a single vortex with the opposite chirality as found in smaller d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Our result is unexpected and intriguing because only c has been considered controllable in asymmetric disks. [24][25][26][27][28] Simultaneous control of c and p is thought to be related to the asymmetric nature in the formation process of vortex states, as reported in our previous work. 7 It was found that two different vortex state groups with cp = +1 and Simultaneous control of magnetic topologies M-Y Im et al cp = − 1 are not energetically equivalent in a single circular disk due to both intrinsic and extrinsic factors.…”
Section: Simultaneous Control Of Magnetic Topologies M-y Im Et Almentioning
confidence: 74%
See 1 more Smart Citation
“…Our result is unexpected and intriguing because only c has been considered controllable in asymmetric disks. [24][25][26][27][28] Simultaneous control of c and p is thought to be related to the asymmetric nature in the formation process of vortex states, as reported in our previous work. 7 It was found that two different vortex state groups with cp = +1 and Simultaneous control of magnetic topologies M-Y Im et al cp = − 1 are not energetically equivalent in a single circular disk due to both intrinsic and extrinsic factors.…”
Section: Simultaneous Control Of Magnetic Topologies M-y Im Et Almentioning
confidence: 74%
“…Thus far, both static and dynamic studies on the control of vortex structures have been primarily dedicated to manipulation of either the c or p alone. 8,[21][22][23][24][25][26][27][28][29][30][31] A few attempts have been made to control both c and p, but these attempts have been conducted without repetition, meaning that only a single event of control has been investigated. 32,33 Therefore, reliability and repeatability for control of both topological features has not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…18,20 In this in-plane magnetization configuration, the restricted nanostructure geometry allows for a good control of topological defect nucleation and propagation processes. [16][17][18][19][20] An ideal system to combine these two concepts of topological defects can be found in weak PMA materials in which stripe domains coexist with a significant in-plane magnetization component. When perpendicular magnetic anisotropy K N becomes smaller than magnetostatic energy (E demag = 2πM 2 s with M s the saturation magnetization), weak stripe domains are nucleated in the system 21 above a critical thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Fractional vortices near sample edges allow us to understand many different situations such as holes within a continuous magnetic layer, 17 vortices in nanodots, 19 or domain wall propagation in magnetic nanowires. 18,20 In this in-plane magnetization configuration, the restricted nanostructure geometry allows for a good control of topological defect nucleation and propagation processes.…”
Section: Introductionmentioning
confidence: 99%
“…A-priori, one would assume that only one type of circularity in asymmetrically shaped disks would be reliably selected as long as the direction of external fields for saturating and releasing the disks is fixed [30][31][32][33] . However, our results show that the final outcome of circularity depends on minute details of the dynamics in the initial stage of the formation process.…”
mentioning
confidence: 99%